Continuous and real-time indoor and outdoor methane sensing with portable optical sensor using rapidly pulsed IR LEDs - Mahbub, Parvez; Noori, Ansara; Parry, John S.; Davis, John; Lucieer, Arko; Macka, Mirek (Talanta (Oxford), 2020)
We designed a simple, portable, low-cost and low-weight nondispersive infrared (NDIR) spectroscopy-based system for continuous remote sensing of atmospheric methane (CH4) with rapidly pulsed near-infrared light emitting diodes (NIR LED) at 1.65 μm. The use of a microcontroller with a field programmable gate array (μC-FPGA) enables on-the-fly and wireless streaming and processing of large data streams (~2 Gbit/s). The investigated NIR LED detection system offers favourable limits of detection (LOD) of 300 ppm (±5%) CH4,. All the generated raw data were processed automatically on-the-fly in the μC-FPGA and transferred wirelessly via a network connection. The sensing device was deployed for the portable sensing of atmospheric CH4 at a local landfill, resulting in quantified concentrations within the sampling area (ca 400 m2) in the range of 0.5%–3.35% CH4. This NIR LED-based sensor system offers a simple low-cost solution for continuous real-time, quantitative, and direct measurement of CH4 concentrations in indoor and outdoor environments, yet with the flexibility provided by the custom programmable software. It possesses future potential for remote monitoring of gases directly from mobile platforms such as smartphones and unmanned aerial vehicles (UAV). [Display omitted] •Portable and low-cost continuous sensing of CH4 proposed for both indoor and outdoor use.•NDIR spectroscopy with rapidly pulsed near-infrared LEDs at 1.65 μm.•User-defined flexible processing of optical output using μC-FPGA.•Limits of detection (LOD) of 0.03% CH4, and precision of ±5%.•CH4 concentration at a landfill found between 0.5 and 3.35%, was cross-validated using GC.